EPIDEMIOLOGICAL PROFILE OF PACIENTS UNDERGOING CARDIAC CATHETERIZATION AT A HEMODYNAMICS UNIT IN NATAL/RN (Fiep Bulletin - online, 2011)
This is an exploratory-descriptive research with prospective data and quantitative approach carried out at the hemodynamics sector of a Private Hospital in Natal/RN aiming to identify epidemiological profile of patients undergoing cardiac catheterization at a hemodynamics unit in Natal/RN. Forty five patients were surveyed using a form with closed questions. Of these, 28 (62.2%) were male, 53.3% were between 51 to 70 years, 39 (86.7%) were Caucasians, 15 (33.3%) finished high school education, 19 (42.2%) have income between 3 and 5 minimum wages and 40 (86.7%) were married. Concerning the Indication for catheterization there was predominance of procedures performed by other reasons 27 (60.0%) and 19 (42.2%) by angina/chest pain. The comorbidity which predominated was High Blood Pressure (HBP) 39 (86.7%). Thus, we can conclude that patients undergoing cardiac catheterization showed having an advanced age, sedentary lifestyle and HBP among other co-morbidities, being the majority attended with angina/chest pain.
Keywords: Cardiac Catheterization; Epidemiological profile; Nursing